Immunogenicity and Safety of 13-valent Conjugated Pneumococcal Vaccine in Patients with Rheumatoid Arthritis - B. T. Batozhargalova; M. P. Kostinov; A. D. Shmitko; G. V. Lukina; D. A. Murtazalieva; E. N. Koltsova; E. V. Zhilyaev (Эпидемиология и вакцинопрофилактика)
Relevance. Pneumococci are among the most common causative agents of severe bacterial infections in humans. The prevalence of invasive pneumococcal infections among people with autoimmune inflammatory rheumatic diseases is 3–4 times higher than in the general population. Aim. To evaluate the effectiveness of vaccination with 13-valent pneumococcal conjugate vaccine (PCV 13) in patients with rheumatoid arthritis (RA). Materials and Methods. The data of scientific publications PubMed, Web of Science, elibrary, the National Inpatient Database of the USA, the Moscow Unified Register of Arthritis, the V. A. Nasonova Research Institute of Rheumatology were used in the review. V. A. Nasonova Research Institute of Rheumatology. Conclusion. In the presented review in adult patients with rheumatoid arthritis (RA) receiving various antirheumatic drugs, the immunogenicity (humoral response, opsonophagocytic activity), safety of vaccines of 13-valent conjugated pneumococcal vaccine (PCV13) was assessed. Based on the data presented, a conclusion was made about the safe management of PCV13 and the formation of antibodies to pneumococcus in RA patients with targeted synthetic disease-modifying antirheumatic drugs (tsDMARDs), biologic (bDMARDs) and Glucocorticoids (GCs < 15 mg daily). Methotrexate (MTX) in RA patients reduced the pneumococcal response and the functional activity of antibodies.